Konstruksi Sistem Otomasi Pompa Air Secara Wireless Menggunakan Modul nRF24L01 Studi kasus : PTPN X PG. Pesantren Baru Kediri - Faisal Natanael Lubis; Gembong Edhi Setyawan; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PTPN X PG. Pesantren Baru is a sugar factory located in Kediri. At the factory it is required workers who have to control the pump, one of them in the sugar production process. Controlled pumps are within 150m - 650m. Based on these problems then created a system that will be able to control the pump wirelessly. The system is called mark pump. As a connector between factory workers with the system, the mark pump uses the interface application on the smartphone. The smartphone app will connect to the central node over the internet network. The central node will connect to the pump node through an intermediate node using the radio module nRF24L01. All nodes use Arduino as microcontroller. At the pump node, the relay is used to disconnect and connect the current at the water pump. During testing, the smartphone sends commands to each pump. The results of the test show that, to control the pump manually it takes an average time of 4.3 minutes. To control the pump using the pump system the average time is 245.2ms. Electricity bill savings to control the pump by using a mark pump system of Rp489, 9 per 4.3 minutes. Based on the questionnaire distributed to 8 factory workers, the result of the agreement level on the questionnaire of 37.5% included in the high category and 62.5% very high category.